Harmony of Nature and Culture: Symbolism and Environmental Education in Ritual - Prasetyo, Sigit Fitro (UIN Sunan Gunung Djati Bandung, 2023)
This study delves into the role of cultural rituals in environmental conservation and local wisdom, with a specific focus on the Sundanese tradition of Ruwatan Leuweung Babakti Mandala Manglayang. This ritual holds immense religious and environmental significance, making it an ideal case study for understanding the potential of rituals in promoting environmental awareness and conservation. The research addresses the social importance of preserving cultural heritage, as well as the scientific relevance of exploring the symbiotic relationship between rituals and environmental education. Employing qualitative methods, including interviews, direct observation, and literature analysis, the study unveils the profound symbolism within Ruwatan Leuweung Babakti Mandala Manglayang, which symbolizes the connection between humans and nature, as well as their spiritual ties. This ritual instills a deep appreciation for the natural environment and encourages the celebration of cultural diversity through these symbols. The findings reveal that the ritual serves as more than just a religious practice, becoming a powerful means of fostering environmental consciousness and preserving local heritage. By shedding light on the significance of cultural rituals in environmental conservation and offering insights into their potential as tools for education, this research contributes to the understanding of the inherent link between culture and nature. The study's emphasis on the importance of preserving local wisdom in the face of global challenges aligns with the journal's interdisciplinary focus on sustainability, culture, and conservation, making it a valuable addition to the literature on environmental studies and cultural preservation.